In Vitro Comparative Effects of Pulpine Mineral, Pulpine NE, and MTA on the Viability, Proliferation, Migration, and Attachment of Stem Cells from Human Exfoliated Deciduous Teeth - Moslemi , Masumeh; Torshabi , Maryam; Khosrozamiri, Mahta (Galen Medical Journal, 2024)
Background: This research aimed to evaluate the impact of Pulpine Mineral, Pulpine NE, and mineral trioxide aggregate (MTA) Angelus on crucial cellular functions, including viability, proliferation, attachment, and migration, in stem cells derived from human exfoliated deciduous teeth (SHEDs). Materials and Methods: In this laboratory-based investigation, SHEDs were exposed to 24-hour extracts from Pulpine Mineral, Pulpine NE, and MTA Angelus, prepared in both freshly mixed and fully set forms, over 24 and 72 hours. The methyl thiazolyl tetrazolium (MTT) assay was used to measure cell viability and proliferation, while a scratch test assessed the extent of cell migration. Scanning electron microscopy (SEM) provided insights into how these materials affected cell morphology and attachment. Data analysis was performed using one-way ANOVA and Tukey’s post-hoc test, with statistical significance set at α=0.05. Results: Among the materials tested, MTA resulted in significantly greater cell viability than the other groups (P<0.05). Interestingly, diluted extracts of set Pulpine Mineral showed comparable viability to MTA after 24 hours (P>0.05). In contrast, Pulpine NE yielded the lowest viability scores (P<0.05). For migration, the MTA group achieved complete scratch closure within 48 hours, whereas Pulpine Mineral facilitated partial migration but did not close the scratch entirely. Cells in the Pulpine NE group exhibited neither proliferation nor migration, as they were entirely non-viable. Conclusion: Pulpine Mineral showed superior biological effects compared to Pulpine NE; however, both Pulpine materials exhibited inferior results compared to MTA Angelus.